Training on Making Assessments and Media Bassed on Technological Pedagogical Content Knowledge (TPACK) in Learning - Hairida, Hairida; T, Ahmad Yani; Enawaty, Eny; Masriani, Masriani; Erlina, Erlina; Rasmawan, Rahmat; Muharini, Rini; Lestari, Ira; Ulfah, Maria; Hartoyo, Agung; Pranata, Rio; Seilendra, Pingkan Ramadhan; Hafiz, Muhammad Iqbal Abdul (STKIP Singkawang, 2023)
The implementation of technology in learning activities, especially evaluation and learning media, has not been implemented optimally. The fact that educators do not assess all of these aspects and are still fixated on conventional assessments and innovative media and assessment designs as demanded by the 21st century, which is rarely done. For this reason, to improve the skills of educators, especially science educators who are members of the Mempawah Regency MGMP, training in making assessments and TPACK-based learning media is needed. The purpose of this activity is to improve the ability of educators to make TPACK-based assessments and media in learning and to describe educators' responses to the socialization activities carried out. This training uses a qualitative descriptive method and the material exposure through practice, discussion, and presentation. The results of the training are known to be very helpful for educators to develop assessments and learning media that are interesting, innovative, and effective for students by utilizing technology that is easily accessible to anyone and increasing the knowledge and creativity of educators regarding the implementation of technology in preparing assessments and learning media specifically for science subjects.